(untitled) (Journal of the College of Basic Education, 2022)
The Technologies of Raku pottery is consider one of Technologies of showing the contemporary and ancient pottery . The Mechanisms of execution this Technologies varying upon the stylish methods for pottery person. beginning from the formula pertain in mud and glass , but Even the final burning . The significance of curvet research is existing with agreement and responding the need of knowledge of our organizations , specially ( our Arab Libraries) to need like these researches , that were narrated by difference foreign languages , and aim to enhance the role of Science and Arts to transform and converting with the concept of pottery that is one of Artistic aspects that gives an important significance for color, where indicate Technology of Raku .But the aim of research bases on the study of Technical Mechanism with American Contemporary Raku pottery privately and finding out its differences from Technologies of Raku in countries effected in serious manner to establish this Technology . The above research is determined on its title (Potter of American Raku) to form the period (1972-2008) as follows -Introduction in Technology concept. -Raku –what is it ? it is significance in American pottery -Raku and Technical Mechanisms (clay and glazs) -Applied patterns (samples)in American contemporary Raku pottery it has been achieved or obtained to the resulted of research that indicated the American Raku Pottery with special feature agree with enhancing the American experiment in research to what is new and in vented.